A low-cost scalable 3D-printed sample-holder for agitation-based decellularization of biological tissues. (November 2020) - Carbonaro, Dario; Putame, Giovanni; Castaldo, Clotilde; Meglio, Franca Di; Siciliano, Katia; Belviso, Immacolata; Romano, Veronica; Sacco, Anna Maria; Schonauer, Fabrizio; Montagnani, Stefania; Audenino, Alberto L.; Morbiducci, Umberto; et al.
Highlights: Novel easy to use, versatile, scalable, and low-cost sample-holder. Reduced duration of the agitation-based decellularization process. Improved decellularization homogeneity. Computational analysis for supporting device design and operating conditions definition. Human skin specimens homogeneously decellularized by fast process. Abstract: Decellularized extracellular matrix is one of the most promising biological scaffold supporting in vitro tissue growth and in vivo tissue regeneration in both preclinical research and clinical practice. In case of thick tissues or even organs, conventional static decellularization methods based on chemical or enzymatic treatments are not effective in removing the native cellular material without affecting the extracellular matrix. To overcome this limitation, dynamic decellularization methods, mostly based on perfusion and agitation, have been proposed. In this study, we developed a low-cost scalable 3D-printed sample-holder for agitation-based decellularization purposes, designed for treating multiple specimens simultaneously and for improving efficiency, homogeneity and reproducibility of the decellularization treatment with respect to conventional agitation-based approaches. In detail, the proposed sample-holder is able to house up to four specimens and, immersed in the decellularizing solution within a beaker placed on a magnetic stirrer, to expose them to convective flow, enhancing the solution transport through the specimens while protecting them. Computational fluid dynamics analyses were performed to investigate the fluid phenomena establishing within the beaker and to support the sample-holder design. Exploratory biological tests performed on human skin specimens demonstrated that the sample-holder reduces process duration and increases treatment homogeneity and reproducibility.